2017
DOI: 10.1123/ijspp.2016-0237
|View full text |Cite
|
Sign up to set email alerts
|

Pacing Strategy During 24-Hour Ultramarathon-Distance Running

Abstract: Purpose: To describe pacing strategy in a 24-h running race and its interaction with sex, age group, athletes' performance group and race edition. Methods: Data from 398 male and 103 female participants of 5 editions were obtained based on a minimum 19.2-h effective-running cut-off. Mean running speed from each hour was normalised to the 24-h mean speed for analyses. Results: Mean overall performance was 135.6 ± 33.0 km with a mean effectiverunning time of 22.4 ± 1.3 h. Overall data showed a reverse J-shaped p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 29 publications
7
44
1
Order By: Relevance
“…Results presented in mean and standard deviation. (Bossi et al, 2017), the present study showed that runners adopted a reverse J-shaped pacing strategy during the VI Rio 24-h Marines Ultramarathon running, regardless of sex and performance level. Thus, runners slowed down the pace during most of the race, after performing a faster start and before spurting at the last 10% of the race.…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…Results presented in mean and standard deviation. (Bossi et al, 2017), the present study showed that runners adopted a reverse J-shaped pacing strategy during the VI Rio 24-h Marines Ultramarathon running, regardless of sex and performance level. Thus, runners slowed down the pace during most of the race, after performing a faster start and before spurting at the last 10% of the race.…”
Section: Discussionmentioning
confidence: 46%
“…We used the total distance covered within the 24 h as a performance indicator. In addition, pacing strategy analysis during this open-loop race was based on the distance completed within the 24 h. Thus, in accordance with previous works investigating the influence of the performance level on running pacing strategy (Lima- Silva et al, 2010;Bossi et al, 2017), we ranked runners according to tercile so that those runners within the lowest and highest tercile were designed as low (LP) and high performance (HP) groups, respectively. We discarded those runners within the intermediate tercile, as this ensured a comparison of pacing strategy profiles between distinguished different performance level groups.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations